2010
DOI: 10.1007/s11434-009-0551-2
|View full text |Cite
|
Sign up to set email alerts
|

Control of morphology and structure of calcium carbonate crystals by heparin

Abstract: Growth control of calcium carbonate crystal by organic chemicals contributes an important part to its mineralizing mechanism and biomimetic preparation. The influence of heparin (HEP) on morphology and structure of calcium carbonate generated by CaCl 2 /Na 2 CO 3 solution was studied by a scanning electron microscope, an X-ray diffraction machine, a Fourier transform infrared spectrophotometer and a fluorescent spectrophotometer. The results showed that the calcite formed in the absence of HEP, while the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In the presence of heparin, besides these diffraction peaks of CaCO 3 calcite crystal, other peaks corresponding to (110), (112), ( 114) and (300) phases of CaCO 3 spherical vaterite crystal also appear, further confirming the coexistence of CaCO 3 calcite crystal and spherical vaterite crystal. The composition, structure and morphology of the CaCO 3 particles obtained in the presence of heparin are consistent with those of the previous report, 23 indicating that heparin has been entrapped into the particles. The content of heparin in CCPs-HP is 2.9% (w/w) determined by the toluidine blue assay.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the presence of heparin, besides these diffraction peaks of CaCO 3 calcite crystal, other peaks corresponding to (110), (112), ( 114) and (300) phases of CaCO 3 spherical vaterite crystal also appear, further confirming the coexistence of CaCO 3 calcite crystal and spherical vaterite crystal. The composition, structure and morphology of the CaCO 3 particles obtained in the presence of heparin are consistent with those of the previous report, 23 indicating that heparin has been entrapped into the particles. The content of heparin in CCPs-HP is 2.9% (w/w) determined by the toluidine blue assay.…”
Section: Resultssupporting
confidence: 91%
“…The previous study indicated that it was the presence of heparin in the nucleation reaction of Ca 2+ and CO 3 22 ions that caused the morphology, size and phase purity of CCPs-HP different from those of pure CaCO 3 particles. 23 Thus, it seems reasonable to assume that the high-density COO 2 and HSO 3 2 group along the heparin backbone would also provide nucleation sites for hydroxyapatite through Ca 2+ ion accumulation. To further support this hypothesis, a fluorescence-labeling assay was carried out, in which CaCO 3 particles containing FITC-labeled heparin were used as the original materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,36,37 Most importantly, polymers can effectively inhibit inorganic particle growth and agglomeration, so as to overcome the disadvantages of uneven dispersion and easy aggregation of NCC in organic/ inorganic composites. 4 Liu et al 38 studied that humic acid was added into the Ca(OH) 2 carbonization system to control the morphology of CaCO 3 and well synthesize CaCO 3 with a specific surface area larger than 50 m 2 g À1 .…”
Section: Introductionmentioning
confidence: 99%
“…A fine crystal-morphology plays an important role in the safety and stability of a material [5][6][7]. Methods for controlling crystal-morphology can therefore be used to regulate nucleation and crystal growth during the crystallization process to increase the production and use of security of energetic materials, and improve their energy output performances [8][9][10][11][12].…”
mentioning
confidence: 99%